2006
DOI: 10.1097/01.hjh.0000200508.10324.8e
|View full text |Cite
|
Sign up to set email alerts
|

Regional disparities of hypertension prevalence and management within Germany

Abstract: The entire distribution of diastolic and systolic blood pressure values was shifted upwards in the north-eastern as compared to the south-western German population samples and the prevalences of hypertension differed accordingly. Despite such substantial epidemiologic differences, the community management of hypertension was of almost identical quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
85
1
19

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(113 citation statements)
references
References 13 publications
8
85
1
19
Order By: Relevance
“…Data for men were not available in this previous survey. The Augsburg MONICA study which included persons aged 25-74 reported an overall lifetime prevalence of 7% in women and 1% in men [25]. In the present study, the 12-month prevalence of osteoporosis was assessed in persons aged 50 years and older and is slightly higher compared to previous studies.…”
Section: Comparison Of Prevalence Of Single Conditions With Results Fcontrasting
confidence: 50%
See 1 more Smart Citation
“…Data for men were not available in this previous survey. The Augsburg MONICA study which included persons aged 25-74 reported an overall lifetime prevalence of 7% in women and 1% in men [25]. In the present study, the 12-month prevalence of osteoporosis was assessed in persons aged 50 years and older and is slightly higher compared to previous studies.…”
Section: Comparison Of Prevalence Of Single Conditions With Results Fcontrasting
confidence: 50%
“…These prevalence estimates are considerably lower than estimates from the 1998 German National Health Interview and Examination Survey (GNHIES 1998) that were based on standardized blood pressure measurements using cut-offs of 140 mmHg/90 mmHg [24]. The prevalence of hypertension based on blood pressure measurements in other German studies ranged from 28.6-38.5% for women, and from 41.4-60.1% for men [25]. Similarly, in GNHIES 34.9% of women and 32.2% of men had serum cholesterol levels exceeding 250 mg/100 ml [24] as compared to 21.8% of women and 19.8% of men reporting a medical history of hyperlipidemia within the past 12 months or current use of lipid lowering in the present study.…”
Section: Comparison Of Prevalence Of Single Conditions With Results Fmentioning
confidence: 62%
“…Surveys conducted in different continents, countries, regions and also populations in the same countries (e.g. Austria, Germany, the United States, China, France, Croatia) have reported significant geographic variations in blood pressure levels [5][6][7][8][9][10][11]. As of the year 2000, 26.4% of the adult population over the age of 20 has hypertension around the world [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that 25 to 35 % of modern populations suffer from this condition [2][3][4]. Hypertension is the major risk factor for the most common cardio vascular diseases which are a major cause for morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%